Meeting Report: 1st International Functional Metagenomics Workshop May 7–8, 2012, St. Jacobs, Ontario, Canada. Issue 1 (January 2013) - Engel, Katja; Ashby, Deborah; Brady, Sean; Cowan, Don; Doemer, John; Edwards, Elizabeth; Fiebig, Klaus; Martens, Eric; McCormac, Dennis; Mead, David; Miyazaki, Kentaro; Moreno-Hagelsieb, Gabriel; et al.
Abstract This report summarizes the events of the 1st International Functional Metagenomics Workshop. The workshop was held on May 7 and 8, 2012, in St. Jacobs, Ontario, Canada and was focused on building an international functional metagenomics community, exploring strategic research areas, and identifying opportunities for future collaboration and funding. The workshop was initiated by researchers at the University of Waterloo with support from the Ontario Genomics Institute (OGI), Natural Sciences and Engineering Research Council of Canada (NSERC) and the University of Waterloo.